THE EFFECT OF WILDLIFE ORANGUTAN PHOTOS IN THE WORLD WILDLIFE FUND FOR NATURE ADVERTISEMENT ON STUDENT AWARENESS ON ENDANGERED ANIMAL CONSERVATION - Novianti, Erlina; Amanda, Silviana; Sanggrawati, Malcheni (Seni Media Rekam ISI Surakarta, 2022)
Orangutans are native to Indonesia that must be preserved because they are on the verge of extinction. One of the non-profit organizations, World Wildlife Fund for Nature (WWF) which involves outside parties with orangutans through campaign using photo media. This study aims to determine the effect of photos of wild orangutans in the WWF advertisement on students' awareness of conserving endangered species. This research uses an approach to study orangutan wildlife photos which are used as WWF advertisement media and use questionnaires for data collection. The results of this study indicate that the quality of orangutan wildlife photos that meet the rules of wildlife photography can convey information and messages effectively according to the WWF advertisement. WWF's advertisement photos can have a positive influence on respondents, which in the end can make them aware to participate in conserving the endangered orangutan.